ANALISIS FOTOLUMINESENSI KARBON DOT DARI DAUN TEH DAN DAUN PEPAYA DENGAN TEKNIK MICROWAVE - Alvin Dior Al Ghifari; Wahyu Pratama Putra; Isnaeni Isnaeni (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2017)
Carbon dot nanoparticles from processed tea leaves and papaya leaves produced using microwave technique have been made. The purpose of this research was to study the change of optical properties of carbon dot nanoparticles luminescence with photoluminescence test. To make carbon dots, processed tea leaves and papaya leaves were extracted using blender and distilled water, then were put in microwave oven for 5, 10, 20 and 40 minutes. Filtering was done for getting homogeneous carbon dot nanoparticles. Photoluminescence test was performed by exciting the colloidal carbon dot with a diode laser at a wavelength of 405 nm. Luminescent light of carbon dot was recorded by spectrometer. In general, luminescent light of carbon dots was cyan. The results of photoluminescence test showed that the luminescence curves of tea leaves and of papaya leaves were different. The sample heating time in microwave also affected the carbon dot luminescence curves. The change in the luminescence curve showed the structure of energy band on the carbon dot. From this study it can be concluded that carbon dot from natural materials can be easily made by microwave technique and photoluminescence technique can analyze the optical properties.Keywords: carbon dots, photoluminescence, tea leaves, papaya leaves.